Anesthesia management of CRS and HIPEC in advanced ovarian cancer with ultra-high intra-abdominal pressure: a case report - Chen, Suli; Lin, Yanjun; Gao, Shuncai; Liu, Shuo; Yang, Zhanmin; Ma, Ruiqing; Lu, Liangyuan (Frontiers in Oncology, 2024)
Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is a leading treatment for advanced ovarian cancer, significantly improving overall survival and disease-free survival. This case involves a patient with peritoneal metastasis and ultra-high intra-abdominal pressure (36 mmHg). CRS + HIPEC induces extensive pathological and physiological changes affecting respiratory, circulatory, renal, coagulation, and metabolic systems. Effective perioperative anesthesia management, including the type and volume of fluids administered, is crucial for optimizing patient outcomes. The complexities of anesthesia management in such cases present significant challenges.